A new Sodalis lineage from bloodsucking fly Craterina melbae (Diptera, Hippoboscoidea) originated independently of the tsetse flies symbiont Sodalis glossinidius - Nováková, Eva; Hypsa, Václav (FEMS microbiology letters, 2007)
Symbiotic bacterium closely related to the secondary symbiont of tsetse flies, Sodalis glossinidius, has been described from the bloodsucking fly Craterina melbae. Phylogenetic analysis of two genes, 16S rRNA gene and component of type three secretion system, placed the bacterium closer to the Sitophilus-derived branch of Sodalis than to the tsetse symbionts. This indicates that the Craterina-derived lineage of Sodalis originated independent of the tsetse flies symbionts and documents the capability of Sodalis bacteria either to switch between different host groups or to establish the symbiosis by several independent events.
Keywords: Molecular Sequence Data; Symbiosis; RNA, Ribosomal, 16S; sekvence aminokyselin; biologická evoluce; Tsetse Flies; Sequence Alignment; membránové glykoproteiny; Biological Evolution; moucha tse-tse; bakteriální geny; Enterobacteriaceae; Bacterial Proteins; Membrane Glycoproteins; RNA ribozomální 16S; zvířata; symbióza; Amino Acid Sequence; fylogeneze; Genes, Bacterial; molekulární sekvence - údaje; Diptera; bakteriální proteiny; sekvenční seřazení; Phylogeny; Animals